Dietary Nitrate Supplementation Is Not Helpful for Endurance Performance at Simulated Altitude Even When Combined With Intermittent Normobaric Hypoxic Training - Sousa, Ana; Viana, João L.; Milheiro, Jaime; Reis, Vítor M.; Millet, Grégoire P. (Frontiers in Physiology, 2022)
Introduction: Training intensity and nutrition may influence adaptations to training performed in hypoxia and consequently performance outcomes at altitude. This study investigates if performance at simulated altitude is improved to a larger extent when high-intensity interval-training is performed in normobaric hypoxia and if this is potentiated when combined with chronic dietary nitrate (NO3-) supplementation. Methods: Thirty endurance trained male participants were allocated to one of three groups: hypoxia (13% FiO2) + NO3-; hypoxia + placebo; normoxia (20.9% FiO2) + placebo. All performed 12 cycling sessions (8 sessions of 2*6x1 min at severe intensity with 1 min recovery and 4 sessions of 4*6*10 s all-out with 20 s recovery) during a 4-weeks period (3 sessions/ week) with supplementation administered 3-2.5 h before each session. Before and after training intervention, participants performed an incremental exhaustion test, a severe intensity exercise bout to exhaustion (Tlim) and a 3 min all-out test (3AOT) in hypoxia (FiO2=13%) with pulmonary oxygen uptake (V ̇O2), V ̇O2 kinetics and vastus lateralis changes in local O2 saturation (SmO2) measured. Results: In all tests, performance was improved to the same extent in hypoxia compared to normoxia, except for SmO2 after Tlim (p=0.04, d=0.82) and 3AOT (p=0.03, d=1.43) which were lower in the two hypoxic groups than in the normoxic one. Dietary NO3- supplementation did not bring any additional benefits. Conclusion: Performance at simulated altitude was not improved to a larger extent when high-intensity interval-training was held in normobaric hypoxia conditions, when compared with normoxic training. Moreover, dietary NO3- supplementation was ineffective to further enhance endurance performance at simulated altitude.